Остров погибших кораблей - Беляев Александр Романович (Библиотека морских приключений, 1993)
Экземпляры: ф.24(2) (20181217) / Инвентарный номер: 26781 / Цена: 900.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 44 / ББК: 84(2Рос=Рус)6